2022
DOI: 10.1111/apha.13868
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring kidney size to interpret MRI‐based assessment of renal oxygenation in acute pathophysiological scenarios

Abstract: Aim: Tissue hypoxia is an early key feature of acute kidney injury. Assessment of renal oxygenation using magnetic resonance imaging (MRI) markers T 2 and T 2 * enables insights into renal pathophysiology. This assessment can be confounded by changes in the blood and tubular volume fractions, occurring upon pathological insults. These changes are mirrored by changes in kidney size (KS). Here, we used dynamic MRI to monitor KS for physiological interpretation of T 2 * and T 2 changes in acute pathophysiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 79 publications
(269 reference statements)
1
31
0
Order By: Relevance
“…It is most probable that the observed changes in T 2 represent the sum of all these effects. In the face of the relatively rigid renal capsule, edema formation and influx of immune cells will result in an 'intrarenal compartment syndrome': as intrarenal pressure increases, intrarenal blood vessels become compressed [29,[44][45][46]. Studies on AAN revealed that the intoxication results in intrarenal vasoconstriction due to acute deficiency of vasodilatory nitric oxide (NO) [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is most probable that the observed changes in T 2 represent the sum of all these effects. In the face of the relatively rigid renal capsule, edema formation and influx of immune cells will result in an 'intrarenal compartment syndrome': as intrarenal pressure increases, intrarenal blood vessels become compressed [29,[44][45][46]. Studies on AAN revealed that the intoxication results in intrarenal vasoconstriction due to acute deficiency of vasodilatory nitric oxide (NO) [47].…”
Section: Discussionmentioning
confidence: 99%
“…T 2 is sensitive to both the free water content in tissue and the amount of paramagnetic deoxygenated hemoglobin (deoxyHb) per tissue volume (voxel). Therefore, T 2 mapping allows the assessment of the degree of tissue edema as well as probing renal BOLD [21][22][23][24][25][26][27][28][29]. DWI, which probes the tissue microstructure through the displacement of water molecules, has been shown to provide specific information on renal tissue and is considered to be a biomarker of MR renal functional imaging [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…These are just a few highlights and by no means an exhaustive overview of manuscripts published in Acta Physiologica on these topics. Furthermore, many manuscripts have been published within these fields over the latest years, including multiple recent works 9–11 …”
mentioning
confidence: 99%
“…Furthermore, many manuscripts have been published within these fields over the latest years, including multiple recent works. [9][10][11] To honor this tradition, we invite you to take part in a special series on the topic of membrane proteins and epithelial transport in physiology and pathophysiology. We look forward to receiving original articles for consideration for publication in this series.…”
mentioning
confidence: 99%
“…As a first example from Neurology, Soldovieri et al are working on personalized options for patients with KCNMA1‐linked channelopathies 5 . Other focus areas are acute and chronic kidney diseases: Cantow et al recently established noninvasive monitoring of kidney size to assess changes in renal oxygenation, 6 while Kresse et al have characterized the EP1 receptor as s high‐potential target for preventing renal fibrosis, findings which may, in a timely manner, translate to clinical care 7 . Lichtenberger and Patzak, 8 as well as Sholokh and Klussmann, 9 in recent publications, provide systematic overviews of recent findings published in Acta Physiologica, which hold the potential to shift the therapy of acute 8 and chronic 9 kidney injury, respectively, from a symptomatic to a causal approach.…”
mentioning
confidence: 99%